A Scoping Review of Flow Research - Peifer, Corinna; Wolters, Gina; Harmat, László; Heutte, Jean; Tan, Jasmine; Freire, Teresa; Tavares, Dionísia; Fonte, Carla; Andersen, Frans Orsted; van den Hout, Jef; Šimleša, Milija; Pola, Linda; et al. (Frontiers in Psychology, 2022)
Flow is a gratifying state of deep involvement and absorption that individuals report when facing a challenging activity and they perceive adequate abilities to cope with it (EFRN, 2014). The flow concept was introduced by Csikszentmihalyi in 1975, and interest in flow research is growing. However, to our best knowledge, no scoping review exists that takes a systematic look at studies on flow which were published between the years 2000 – 2016. To develop this scoping review, we followed the steps proposed by Arksey and O’Malley (2005). Overall, 253 studies have been included in this review. Our review (1) provides a framework to cluster flow research, (2) gives a systematic overview about existing studies and their findings, and (3) provides an overview about implications for future research. The provided framework consists of three levels of flow research. In the first “Individual” level are the categories for personality, motivation, physiology, emotion, cognition and behavior. The second “Contextual” level contains the categories for contextual and interindividual factors and the third “Cultural” level contains cultural factors that relate to flow. Using our framework, we systematically present the findings for each category. While flow research has made progress in understanding flow, in the future, more experimental and longitudinal studies are needed to gain deeper insights into the causal structure of flow and its antecedents and consequences.